EFFECT OF ADDING DIETARY ROSEMARY LEAVES ON IN VITRO METHANE PRODUCTION AND SOME RUMEN FERMENTATION TRAITS - M.S. Abdulhameed; S. M. Eidan (The Iraqi Journal of Agricultural science)
This study aimed to examine how including dietary dried rosemary leaves (DRL) of Holstein bulls affects methane production and certain rumen fluid characteristics in vitro. Rumen fluid was obtained from newly slaughtered calves and used in two separate trials: one for gas production and another for digestion. In the trials, two diets were implemented. The first was the standard diet for bulls, consisting of a concentrate diet and alfalfa hay (control group). The second diet included the addition of 250 g DRL to the essential diet. There was a significant decrease (P≤0.01) in methane and N-NH3 production, as well as in the ratio between unsaturated fatty acids (USF) and saturated fatty acids in the rosemary group compared to the control. In the first trial, the concentrations of both volatile and non-volatile fatty acids as well as the total USF increased significantly (P≤0.01) in the rosemary group compared to the control group. In the second trial, there was a significant increase (P≤0.01) in the digestibility of dry and organic matters and in metabolizable energy in the rosemary group. There was a decrease in the population of protozoa in the rosemary group compared to the control group. The addition of DRL can be seen as beneficial in modifying rumen fermentation. This can lead to a reduction in methane production and an improvement in rumen fermentation traits. As a result, there is an increase in the undegradable protein in the rumen that enters the small intestine. This ultimately means that more amino acids are available for production, and methane emissions from bulls can be reduced, contributing to sustainable agricultural development goals.